Síntese e caracterização de materiais luminescentes de composição SrTiO3:Pr,La - Deltreggia, Lucas Angelini [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Strontium Titanate, SrTiO3, is a material of peroviskta structure that has been applied as a luminophore. It is already known in the literature that the incorporation of rare earth ions in the site occupied by Sr provoke significant changes in its structural properties and produce luminescent effects in the visible range. However, few studies report the insertion of La in the Sr site, with respect to the structural and luminescent characteristics of this compound. In this way, the present work studies the photoluminescent properties presented by the matrix based on Strontium Titanate, doped with Praseodymium (Pr) and Lanthanum (La). The material was synthesized by the polymeric precursor method, which proved effective for the preparation of the desired structural characterization. The X-ray diffraction technique allowed to identify that all the samples are present in the crystalline phase and exhibit orthorhombic symmetry. It was possible to observe, through the X-ray absorption spectroscopy at the edge K of the Ti, the occurrence of greater Ti symmetry with respect to the O atoms around it when the calcination temperature was increased and that the substitution of ions at the Sr site does not change such symmetry. In the luminescence spectra it was observed that the increase of the density of structural defects favors the increase of the intensity of light emission as a function of the concentration of La, since such insertion cuases vacancies in the material that contribute to the improvement in the emission of lightspectrum

O Titanato de Estrôncio, SrTiO3, é um material de estrutura peroviskta que tem sido aplicado como luminóforo. Já é sabido pela literatura que a incorporação de íons terra rara no sítio ocupado pelo Sr provocam mudanças significativas nas suas propriedades estruturais e produzem efeitos luminescentes na faixa do visível. Porém, poucos trabalhos reportam a inserção de La no sítio do Sr, no que diz respeito às características estruturais e luminescentes desse composto. Desta forma, o presente trabalho estuda as propriedades fotoluminescentes apresentadas pela matriz à base de Titanato de Estrôncio, dopada com Praseodímio (Pr) e Lantânio (La). O material foi sintetizado pelo método dos precursores poliméricos, que se mostrou efetivo para a preparação da caracterização estrutural desejada. A técnica de difração de raio X permitiu identificar que todas as amostras apresentam-se na fase cristalina e exibem simetria ortorrômbica. Foi possível constatar, através da espectroscopia de absorção de raio X na borda K do Ti, a ocorrência de maior simetria do Ti em relação aos átomos de O ao seu redor quando aumentada a temperatura de calcinação e que a substituição de íons no sítio do Sr não altera tal simetria. Nos espectros de luminescência observou-se que o aumento da densidade de defeitos estruturais favorece o aumento da intensidade de emissão de luz em função da concentração de La, uma vez que, tal inserção provoca vacâncias no material que contribuem para a melhora na emissão de espectroluminoso
Keywords: Fisica moderna; Raios X - Difração; Titanato; Estrôncio; Lantanio; Luminescencia; Fotoluminescencia